Improved Bee keeping in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CCAFS East African regional program selects six sites to test interventions that address risks related to climate change and variability. Featured here is the Lower Nyando, Kenya site, where farmers are introduced to improved bee keeping activities as a way to diversify their farming activities and in the long-term will help create resilience to climate change and improve livelihoods and incomes in the community. Photo: K. Trautmann Please credit accordingly.